International judicial review : when should international courts intervene? - Dothan, Shai (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"The book is motivated by a question: when should international courts intervene in domestic affairs? To answer this question thoroughly, it is broken down to a series of separate inquiries: When is intervention legitimate? When can international courts identify good legal solutions? When will intervention initiate useful processes? When will it lead to good outcomes? These inquiries are answered based on reviewing judgments of international courts, strategic analysis, and empirical findings. The book outlines under which conditions intervention by international courts is recommended and evaluates the implications international courts have on society"--
The argument from normative legitimacy -- The argument from systemic epistemic superiority -- Why international courts improve deliberation -- Who should participate in the courts' proceedings? -- Creating the right incentives.
Includes bibliographical references (pages 143-156) and index.
Keywords: International courts; Judicial review; Jurisdiction (International law); Tribunaux internationaux; Controle juridictionnel des lois; Juridiction (Droit international); Review (function); Judicial review; International courts; Jurisdiction (International law); International courts; Jurisdiction; International law and national law